Partisipasi Masyarakat Dalam Meningkatkan Mutu Pendidikan Di SDN Kumalasa Sangkapura Bawean Gresik - M, Ansharuddin; sholihan, Sholihan (Universitas Nahdlatul Ulama Sunan Giri, 2023)
This research discusses community participation in improving the quality of education at SDN Kumalasa Sangkapura Bawean Gresik. This problem is described into several focus problems, first How is community participation in improving the quality of education at SDN Kumalasa Sangkapura Bawean Gresik? Second, what factors support participation in improving the quality of education at SDN Kumalasa Sangkapura Bawean Gresik? This research aims to determine community participation in improving the quality of education at SDN Kumalasa Sangkapura Gresik. And to find out the factors that support and hinder community participation in improving the quality of education at SDN Kumalasa Sangkapura Bawean Gresik. This research uses a qualitative approach with a descriptive type, data collection methods are carried out through observation, interviews and documentation techniques with the informants being the school principal, teachers, school committee, community elements and parents. Data analysis uses reduction display and verification techniques. Currently checking the validity of the data using source triangulation. The results of this research state that firstly, community participation in improving the quality of education at SDN Kumalasa Sangkapura Bawean Gresik is very good by providing assistance in physical and non-physical forms. Physical assistance in the form of funds, goods, procurement and maintenance of facilities and infrastructure, teachers and personnel. Non-physical assistance in the form of thoughts, ideas, suggestions, constructive criticism, motivation and curriculum. The two factors that support community participation are community traditions, beliefs (religion), form of government, and leadership model. The inhibiting factors are the level of education and economic conditions of the community.